FRI0384 A mini-invasive technique for haemodynamic evaluation: new perspectives for pulmonary arterial hypertension (PAH) diagnosis in systemic sclerosis (SSC). (15th June 2017) - Bellucci, E; Romano, MS; Chiostri, M; Bruni, C; Giglioli, C; Bernardo, P; Conforti, ML; Bellando-Randone, S; Guiducci, S; Matucci-Cerinic, M
Abstract : Background: PAH is one of the most severe complication and cause of mortality in SSc, with frequent late diagnosis as asymptomatic in its early stages. Right Heart catheterization (RHC) is the gold standard for PAH detection, though its invasive nature with high risk of procedure related complications stress the need for developing new screening methods to investigate it in early and possibly reversible stages. Pressure Recording Analytical Method (PRAM) was recently developed to obtain a minimally invasive haemodynamic monitoring, using an arterial line and proximal pulsossimetry. This analyses arterial blood pressure curve and measure both cardiac [Cardiac Index, Cardiac Contractility and Vascular Stiffness ratio (dP/dT)] and vascular [vascular stiffness, elastance], which can be usually obtained only through RHC. Objectives: to evaluate the clinical usefulness of PRAM method in SSc patients and to identify haemodynamic parameters related to increased risk of developing PAH. Methods: 40 ssc patients (35 women, mean age 60±9, 3 years; mean disease duration 7.5 years) were evaluated with both RHC and PRAM on the same day. Mean pulmonary arterial pressure (mPAP), cardiac index (CI), systemic vascular resistances (SVR), right cardiac power index (RCPI, calculated with mPAPXCIPRAM /451) were measured and concordance of the two methods was assessed through Bland-Altmann analysis. Systolic pulmonary arterial pressure and TAPSE from echocardiography, forced vital capacity, total lung capacity, both absolute and alveolar volume adjusted Carbone oxide lung diffusion (DLCO and DLCO/VA) from pulmonary function tests, blood tests parameters, nailfold videocapillaroscopy scleroderma patterns were recorded. Univariate and multivariate logistic regression analysis identified variables correlating with RHC-diagnosed PAH: a scoring system was then created, giving 1 point for value satisfying cut-off level. Results: PRAM showed concordance with RHC estimate of CI and SVR within 95% interval confidence; 14 patients were diagnosed with PAH (mean age 64, 4±9, 3, mean disease duration 10.5 years, lSSc 61, 5%). Multivariate logistic regression analysis showed DLCO (cut off value 47% obtained through ROC curve analysis, p=0.004) and RCPI (cut off value 0.12 Watt obtained through ROC curve analysis, p<0.001) as the most highly PAH-associated variables. When combining these two variables in the scoring system, patient with score=0 (DLCO<47% and RCPI<0, 12 Watt), score=1 (DLCO<47% or RCPI≥0, 12 Watt) and score=2 (DLCO<47% and RCPI≥0, 12) were 0%, 21.4% and 78.6% of the PAH population respectively. Conclusions: PRAM is comparable to RHC in detecting haemodynamic parameters such as SVR and CI. The scoring system combining DLCO and RCPI, obtained with non-invasive tools, could offer the possibility of detecting PAH patients with a high specificity. Disclosure of Interest: None declared